2022
DOI: 10.3390/land11112042
|View full text |Cite
|
Sign up to set email alerts
|

Micrometeorological and Hydraulic Properties of an Urban Green Space on a Warm Summer Day in a Mediterranean City (Attica–Greece)

Abstract: Urban Green Spaces (UGSs) are considered the most effective tool to mitigate Urban Heat Islands (UHIs). The optical properties of the materials and the vegetation types of the UGSs affect their surface temperatures, directly influencing their cooling ability. The hydraulic properties of urban soils are also affected by the vegetation coverage. The aim of this study is to investigate the temperature and reflected radiation (albedo) differences between UGS’s elements, around noon on a warm summer day, in Greece.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The soil moisture per volume was recorded by a delta-t SM150 sensor. To estimate the unsaturated hydraulic conductivity, a minidisk infiltrometer (Meter Group) was used according to Zhang's [7] methodology [8].…”
Section: Methodsmentioning
confidence: 99%
“…The soil moisture per volume was recorded by a delta-t SM150 sensor. To estimate the unsaturated hydraulic conductivity, a minidisk infiltrometer (Meter Group) was used according to Zhang's [7] methodology [8].…”
Section: Methodsmentioning
confidence: 99%
“…City greening through various means such as street trees (Cohen et al, 2012), courtyard gardens (Tsiros & Hoffman, 2014) and urban parks (Graça et al, 2022;Oliveira et al, 2014;Proutsos et al, 2022;Saaroni et al, 2015bSaaroni et al, , 2018Sera et al, 2019), as well as reflective and green roof technologies (Alcazar et al, 2016;Karteris et al, 2016;Santamouris, 2014;Silva et al, 2016), is widely recognized as beneficial for urban heat mitigation. Street-level shading to mitigate exposure to shortwave radiation is the dominant element for enhancing thermal comfort in public spaces (Aleksandrowicz & Pearlmutter, 2023).…”
Section: Thermal Stress and Air Qualitymentioning
confidence: 99%
“…The climate of the broader area is characterized as semi-arid [47][48][49], according to UNEP's [50] aridity climate classification system based on Thornthwaite's [51,52] water balance approach. A detailed description of the study site can be also found in Proutsos et al [43] and in Solomou et al [53].…”
Section: Study Sites and Instrumentationmentioning
confidence: 99%
“…In a recent study by Zhou et al [41], the authors describe the complex heat storage and shading effects in the urban environment, underlining also that only neglecting the shading effects leads to an overestimation of urban evapotranspiration of about 38.7%. In addition, the variable reflectance characteristics of the urban surfaces (even green ones) and surface temperatures in association with urban heat island and drought phenomena are highly affecting ET [42][43][44] in the cities.…”
Section: Introductionmentioning
confidence: 99%